(untitled) (Eurasian Journal of Engineering and Technology, 2023)
Blood donation saves people’s lives every day in various situations. Compared to the actual need, extremely few people donate blood. This study introduces a proposed System for managing blood donation in rural areas. Any hospital, blood bank, or medical facility that employs blood banks can employ a blood bank management system. This study’s primary objective is to suggest a blood donor management system specifically for third-world rural environments. Firstly, a web application developed using the appropriate Server and Client-side scripting languages. Secondly, an Android application was developed to be installed on the donor’s mobile. The goal of such systems is to stop the anxiety brought on by a blood shortage in an emergency. In an emergency, the proposed system can locate the necessary amount of blood from a blood bank or even a blood donor. The proposed system provides a service for the donor to communicate directly with the patient who needs blood, and the patient can search in the nearby area to invest time that could contribute to saving the patient’s life